PELAKSANAAN PENDAFTARAN HAK MILIK ATAS TANAH MELALUI PROYEK OPERASI NASIONAL AGRARIA (PRONA) DI KABUPATEN GIANYAR - Agus Eka Kurniawan, Putu; Dunia, Ngakan Ketut; Darmadha, I Nyoman (Kertha Negara : Journal Ilmu Hukum; Vol. 01, No. 05, Juli 2013)
This study aims at investigating the implementation of land certificate program through PRONA in Gianyar regency and constraints encountered in implementation. This research belongs to kind of empirical legal research that examines the various regulations on the National Agrarian Operations Project Program (PRONA) in the process, in their interactions, and their application as well as their influence in society. This descriptive study use 2 (two) types of data sources, namely primary data and secondary data. The samples in this study were Gianyar Land Office that was determined through non probability sampling technique that is purposive sampling. The obtained data in this study were analyzed qualitatively and then presented descriptively. Based on the land certificate publishion target for each PRONA participant village in Gianyar regency Fiscal Year of 2011, the realization has met the target is, that are 618 certificate for Lodtunduh village or 100%, 330 certificate for Medahan village or 100%,252 certificate for Siangan village or 100%. The implementation of PRONA of land office in Gianyar regency in Fiscal Year 2011 is carried get through preparation process and land registration process. The Constraints in during the land certification program through PRONA can be viewed from village community side as PRONA participant and Gianyar land office as well.
Keywords: land registration, PRONA, sertificate